Using short stories in teaching English in the context of Vietnam Australia School - Hanoi - Phạm, Thu Hà (ĐHNN, 2017)
Chapter 1, Introduction,briefly presents the reasons for doing the study, its aims, scope, subjects as well as the research methodology. Chapter 2, Literature review,presents an overview of literature and short stories in language teaching. Chapter 3, Methodology,states the reason for choosing research methodology and the descriptions of the setting, subjects, instruments and the procedure of data collection and analysis. Chapter 4, Data analysis and Results,provides an analysis of collected data and the findings.Chapter 5, Conclusion and recommendations, suggests teaching techniques and conclusion